The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1530/jrf.0.1110065
|View full text |Cite
|
Sign up to set email alerts
|

Survival and development of bovine blastocysts produced in vitro after assisted hatching, vitrification and in-straw direct rehydration

Abstract: The purpose of this study was to establish an efficient combination of assisted hatching and cryopreservation procedures for producing bovine embryos in vitro. A total of 1312 day 7 blastocysts were subjected randomly to 14 different combinations of three factors: osmotic stress, assisted hatching and vitrification. Re-expansion, initiation and completion of the hatching process, as well as attachment to the culture dish, were analysed by SAS Genmod procedure. Incubation with sucrose was found to decrease surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…On the other hand pregnancy rates following transfer of programmable frozen compact morulae, early blastocysts, blastocysts and expanded blastocysts regardless of quality grades were 29%, 50%, 33% and 50%, respectively. Analogous to our observations, the studies of Vajta et al (1997bVajta et al ( , 1998aVajta et al ( , 1999 and Lazar et al (2000) demonstrated that advanced stages of in vitro produced bovine embryos can be vitrified successfully with hatching rates reaching 60% to 94%. Even in vitro produced embryos vitrified at the hatched blastocyst stage reached up to 81% re-expansion rate after 24 h of culture.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand pregnancy rates following transfer of programmable frozen compact morulae, early blastocysts, blastocysts and expanded blastocysts regardless of quality grades were 29%, 50%, 33% and 50%, respectively. Analogous to our observations, the studies of Vajta et al (1997bVajta et al ( , 1998aVajta et al ( , 1999 and Lazar et al (2000) demonstrated that advanced stages of in vitro produced bovine embryos can be vitrified successfully with hatching rates reaching 60% to 94%. Even in vitro produced embryos vitrified at the hatched blastocyst stage reached up to 81% re-expansion rate after 24 h of culture.…”
Section: Discussionsupporting
confidence: 86%
“…In addition vitrification is suitable for freezing of bovine embyos in the precompaction stage (Vajta, 2003) or advanced stages of embryos as in vivo or in vitro produced hatched blastocysts (Vajta et al, 1997b). Use of vitrification has been increased by the development of vitrification in open pulled straws (OPS).…”
mentioning
confidence: 99%
“…The results of our in vitro and in vivo experiments are consistent with those published by Schiewe et al (1995) who used a mouse model and found higher hatching rates (p < 0.01), but no significant difference in implantation rates after AH treatment. Significant differences in the development between embryos with mechanically or laser-treated and non-treated zona were reported by Park et al (1999) and Vajta et al (1997) who cultured bovine blastocysts in vitro (IVM/IVF/IVC). We assume that the equal survival rate found in our experiments for zona-slit and nontreated fresh grade 1 embryos is attributable to the cell number and the quality of the embryonic cell complex with the natural expansion and hatching potentials.…”
Section: Discussionmentioning
confidence: 91%
“…This is accomplished by direct immersion into liquid nitrogen of open-pulled straws containing small droplets (typically 1-20 µl) of vitrification solution within which the colony fragments (< 10) are held. Straws are then generally transferred to liquid nitrogen for long term storage (Vajta et al, 1997;Vajta et al, 1998).…”
Section: Vitrification and Optimizations Of The Techniquementioning
confidence: 99%